1979
DOI: 10.1111/j.1471-4159.1979.tb05236.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Regulates via Two Different Types of Receptors, the Accumulation of Cyclic Amp in Cultured Brain Cells

Abstract: In cell cultures of glial character derived from perinatal mouse brain adenosine elicits two effects. (a) At submicromolar concentrations I t inhibits the increase in the intracellular level of cyclic AMP caused by j-adrenoceptor agonists. (b) At concentrations above micromolar it increases the level of cyclic AMP in the cultures. These two effects are mediated by two different adenosine receptors present on the outer surface of the cells. This is concluded from the following evidence. (a) Both effects are ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
442
1
4

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,279 publications
(472 citation statements)
references
References 32 publications
(14 reference statements)
25
442
1
4
Order By: Relevance
“…Theincubations were terminated by removal of the buffer and the addition of 1 ml ice-coJd trichloroacetic acid (10% w jv). After removal of the trichloroacetic acid by extraction with diethyl ether (3 times 4 ml), the samples were fractionated by anion chromatography on small Dowex columns (Bio Rad AG 1 X 2) as described (Van Calker et al, 1979). The cyclic AMP content in the samples was determined by a commercially available protein binding assay (Amersham).…”
Section: Determination Of Cyclic Ampmentioning
confidence: 99%
See 1 more Smart Citation
“…Theincubations were terminated by removal of the buffer and the addition of 1 ml ice-coJd trichloroacetic acid (10% w jv). After removal of the trichloroacetic acid by extraction with diethyl ether (3 times 4 ml), the samples were fractionated by anion chromatography on small Dowex columns (Bio Rad AG 1 X 2) as described (Van Calker et al, 1979). The cyclic AMP content in the samples was determined by a commercially available protein binding assay (Amersham).…”
Section: Determination Of Cyclic Ampmentioning
confidence: 99%
“…Astrohlast cultures were prepared by mechanical dissociation of newborn mouse or rat brain and cultivated as described previously (Van Calker et al, 1979).…”
mentioning
confidence: 99%
“…Adenosine A 1 -and A 2 -receptor subtypes were originally distinguished by their differential effects on adenylyl cyclase (van Calker et al 1978(van Calker et al , 1979, but more recent findings have revealed coupling of adenosine receptors to other signal transduction systems including phospholipase C (PLC) (Miller and Hoffman 1994;Fredholm et al 1994). Very often, the coupling of adenosine A 1 -receptors to PLC ␤ is synergistic with the stim- NO .…”
Section: The Anticonvulsant and Antibipolar Drug Carbamazepine (Cbz) mentioning
confidence: 99%
“…CBZ may even have advantages as compared to lithium in the treatment and prophylaxis of schizoaffective and rapid cycling bipolar disorders (for review see Solomon et al 1995). Among the various pharmacological effects of CBZ, its activity as a specific antagonist at adenosine A 1 receptors (van Calker et al 1991;Biber et al, 1996) may be particularly important, because this property could lead to alterations in the responsiveness of signal transduction systems in the brain (van Calker et al 1998), a mechanism believed to be instrumental also to lithium's beneficial effects in affective disorders (for review see Manji et al 1995).Adenosine A 1 -and A 2 -receptor subtypes were originally distinguished by their differential effects on adenylyl cyclase (van Calker et al 1978(van Calker et al , 1979, but more recent findings have revealed coupling of adenosine receptors to other signal transduction systems including phospholipase C (PLC) (Miller and Hoffman 1994;Fredholm et al 1994). Very often, the coupling of adenosine A 1 -receptors to PLC ␤ is synergistic with the stim- NO .…”
mentioning
confidence: 99%
See 1 more Smart Citation